Analysis and design of information systems - Rajaraman, V. (Prentice Hall, 1991)
This book is ideally suited for courses in information systems analysis and design which is a compulsory for the DCA, MCA dan BE (Computer Science) examinations. Besides, it should help those students appearing for the proficience examination on system analysis and design conducted by the Computer Society of India. Practitioners in the area should also find it useful.